Physics potential of the International Axion Observatory (IAXO) - Armengaud, Eric; Gastaldo, Loredana (Journal of cosmology and astroparticle physics, 2019)
We review the physics potential of a next generation search for solar axions: the International Axion Observatory (IAXO). Endowed with a sensitivity to discover axion-like particles (ALPs) with a coupling to photons as small as $g_{aγ}\sim 10^{-12}$ GeV$^{-1}$, or to electrons $g_{ae}\sim$10$^{-13}$, IAXO has the potential to find the QCD axion in the 1 meV$\si
Gesehen am 16.08.2019